Method for treating activated carbon and electricity storage device

By heat-treating activated carbon with a carbon source to adsorb gaseous carbon on its surface, the issues of gas generation and high resistance are mitigated, resulting in low-resistance electrodes for power storage devices.

JP2025003392APending Publication Date: 2025-01-09AKECHI CERAMICS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024099439
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-22
Filing Date
2024-06-20
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Activated carbon's high specific surface area and adsorption ability lead to gas generation and high electrical resistance, making it difficult to use as an electrode in power storage devices, necessitating the use of conductive additives.

Method used

Simultaneously heat-treating activated carbon with a carbon source that generates gaseous carbon, allowing the thermally decomposed carbon to be adsorbed and attached to the surface, thereby reducing adsorption capacity and electrical resistance.

Benefits of technology

The treated activated carbon exhibits reduced gas generation, maintains specific surface area, and achieves lower resistance, enabling high-performance electrodes in power storage devices without the need for conductive additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025003392000001_ABST
    Figure 2025003392000001_ABST
Patent Text Reader

Abstract

To provide a method for treating activated carbon capable of reducing gas generation by suppressing the adsorption capacity of activated carbon, and an electricity storage device using activated carbon treated by the method as an electrode.SOLUTION: In a method for treating activated carbon, activated carbon 1 and a carbon source 2 that generates vapor-phase carbon upon heating are simultaneously heat treated, and the thermally decomposed carbon source 2 is adsorbed and attached to the surface of the activated carbon 1. The electricity storage device 10 of this invention is a device for storing electricity that uses, as an electrode, the activated carbon 1 treated by the method.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for treating activated carbon and an electricity storage device that uses, as an electrode, activated carbon treated by the method for treating activated carbon. [Background technology]

[0002] Conventionally, activated carbon has a large specific surface area and is used for the positive and negative electrodes of electric double layer capacitors or the positive electrodes of lithium ion capacitors (for example, JP 2022-55902 A).

[0003] However, activated carbon has a large specific surface area and a high surface adsorption capacity, which causes problems such as the generation of adsorbed gas during operation. In addition, low resistance is an important factor for the electrodes of electricity storage devices, but activated carbon is amorphous carbon, and therefore has high electrical resistance among carbon materials, which is a concern. Therefore, it is essential to use a conductive additive in order to use it as an electrode. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2022-55902 Summary of the Invention [Problem to be solved by the invention]

[0005] Therefore, an object of the present invention is to provide a method for treating activated carbon that can suppress the adsorption capacity of activated carbon and reduce gas generation, and an electricity storage device that uses activated carbon treated by the method for treating activated carbon as an electrode. [Means for solving the problem]

[0006] The above-mentioned problem is solved by a method for treating activated carbon, which comprises simultaneously heat-treating activated carbon and a carbon source that generates gaseous carbon when heated, and adsorbing and attaching the pyrolyzed carbon source to the surface of the activated carbon (Claim 1).

[0007] The activated carbon obtained by the activated carbon treatment method preferably has the same pore profile as the activated carbon before the treatment (Claim 2). It is preferable that the carbon source has a low resistance when the pyrolyzed carbon source adheres to the surface of the activated carbon (Claim 3).

[0008] The carbon source is preferably raw coke (claim 4). The temperature of the heat treatment is preferably 450 to 1200° C. (claim 5). Moreover, the temperature of the heat treatment is more preferably 800 to 1100° C. (claim 6).

[0009] The above problem is also solved by an electricity storage device characterized in that the activated carbon having a carbon source attached to the surface thereof, which generates gaseous carbon when heated, is used as an electrode (claim 7).

[0010] The carbon source is preferably raw coke (Claim 8). The activated carbon is preferably heat-treated simultaneously with the carbon source, so that the pyrolyzed carbon source is adsorbed and attached to the surface of the activated carbon, and the activated carbon has the same pore profile as the activated carbon before the treatment and has low resistance (Claim 9). The electricity storage device is preferably an electric double layer capacitor, a lithium ion capacitor, or an air battery (Claim 10). The electricity storage device is an electric double layer capacitor according to Claim 7, which has low internal resistance even at low temperatures and small change in capacitance value relative to current density, compared to an electricity storage device using untreated activated carbon as an electrode before a carbon source that generates gaseous carbon when heated is attached to the surface of the activated carbon (Claim 11). Effect of the Invention

[0011] According to the activated carbon treatment method recited in claim 1, the adsorption capacity of the activated carbon can be suppressed, thereby reducing gas generation. According to the method for treating activated carbon recited in claim 2, it is possible to suppress a decrease in the specific surface area caused by coating. According to the activated carbon treatment method described in claim 3, it is possible to produce an electrode for an electricity storage device that has a small IR drop on both the charging and discharging sides, shows a good charge / discharge curve, and can maintain capacity even if the current density increases or if no conductive additive is used. According to the method for treating activated carbon set forth in claim 4, activated carbon having the effect of claim 1 can be more easily produced. According to the method for treating activated carbon set forth in claim 5, activated carbon having the effect of claim 1 can be produced more reliably. According to the method for treating activated carbon described in claim 6, in addition to the effect of claim 1, a low resistance film can be more reliably formed on the surface of the activated carbon. According to the electricity storage device recited in claim 7, a high-performance electricity storage device is configured using electrodes with reduced adsorption ability. According to the electricity storage device recited in claim 8, the electricity storage device having the effect of claim 7 can be easily manufactured. According to the electricity storage device described in claim 9, in addition to the effect of claim 7, an electricity storage device is produced which has a small IR drop on both the charging side and the discharging side, exhibits a good charge / discharge curve, and can maintain capacity even when the current density increases or when no conductive additive is used. According to the electricity storage device recited in claim 10, a higher performance electric double layer capacitor, lithium ion capacitor or air battery is constituted, in which activated carbon with reduced adsorption capacity is used for the electrodes. According to the electricity storage device of the present invention, the internal resistance is lower even at low temperatures and the change in capacitance value relative to the current density is smaller than that of an electric double layer capacitor using the activated carbon before treatment as an electrode. [Brief description of the drawings]

[0012] [Figure 1]FIG. 2 is an explanatory diagram for explaining one embodiment of a treatment method for activated carbon according to the present invention. [Diagram 2] 2 is a table comparing the results of evaluation test 1 of low-resistance activated carbon (Pyrocoat) obtained by the activated carbon treatment method shown in FIG. 1 and activated carbon (untreated) of a comparative example. [Diagram 3] 2 is a graph comparing the results of an evaluation test (pore distribution analysis results by the BJH method) of the low-resistance activated carbon (Pyrocoat) obtained by the activated carbon treatment method shown in FIG. 1 and the activated carbon (untreated) of a comparative example. [Figure 4] 2 is a graph comparing the results (micropore analysis results by the HK method) of evaluation test 1 of low-resistance activated carbon (Pyrocoat) obtained by the activated carbon treatment method shown in FIG. 1 and the activated carbon (untreated) of a comparative example. [Diagram 5] FIG. 2 is an explanatory diagram for explaining a method of evaluation test 2 of the low-resistivity activated carbon (Pyrocoat) obtained by the activated carbon treatment method shown in FIG. 1 and the activated carbon (untreated) of a comparative example. [Figure 6] 2 is a table comparing the results of evaluation test 2 of low-resistance activated carbon (Pyrocoat) obtained by the activated carbon treatment method shown in FIG. 1 and activated carbon (untreated) of a comparative example. [Figure 7] 2 is a graph comparing the results (test force) of evaluation test 2 of low-resistance activated carbon (Pyrocoat) obtained by the activated carbon treatment method shown in FIG. 1 and activated carbon (untreated) of a comparative example. [Figure 8] 2 is a graph comparing the results (resistance values) of evaluation test 2 of low-resistance activated carbon (Pyrocoat) obtained by the activated carbon treatment method shown in FIG. 1 and activated carbon (untreated) of a comparative example. [Figure 9] FIG. 1 is a schematic diagram for explaining an embodiment of an electricity storage device of the present invention. [Figure 10] 1 is a graph showing the charge / discharge characteristics of an electricity storage device according to Comparative Example 1 (untreated: without conductive additive). [Figure 11] 1 is a graph showing the charge / discharge characteristics of Example 1 of the electricity storage device of the present invention (low-resistance activated carbon: no conductive additive). [Figure 12]1 is a table showing the results of measuring the capacity of an electricity storage device according to Comparative Example 2 (untreated activated carbon: conductive additive added) and an electricity storage device according to Example 2 (low-resistance activated carbon: conductive additive added). [Figure 13] 1 is a graph showing charge / discharge curves of Example 3 of the electricity storage device of the present invention (low-resistance activated carbon: conductive assistant added). [Figure 14] 1 is a graph showing charge / discharge curves of Example 3 of the electricity storage device of the present invention (low-resistance activated carbon: conductive assistant added). [Figure 15] 1 is a graph comparing the capacity retention rates of electricity storage devices of Comparative Examples 2 and 3 (untreated activated carbon: conductive assistant added) and electricity storage devices of Examples 2 and 3 of the present invention (low-resistance activated carbon: conductive assistant added). [Figure 16] 1 is a graph showing charge / discharge curves (at room temperature of 25° C. and current densities of 80 mA / g and 500 mA / g) of an electricity storage device according to Comparative Example 4 (in which untreated activated carbon was used as an electrode). [Figure 17] 1 is a graph showing charge / discharge curves (at room temperature of 25° C. and current densities of 80 mA / g and 500 mA / g) of Example 4 of the electricity storage device of the present invention (wherein low-resistance activated carbon is used as an electrode). [Figure 18] 1 is a table showing the results of measuring the capacity at room temperature of 25° C. and current densities of 80 mA / g and 500 mA / g for an electricity storage device according to Comparative Example 4 (in which untreated activated carbon was used as an electrode) and an electricity storage device according to Example 4 of the present invention (in which low-resistance activated carbon was used as an electrode). [Figure 19] 1 is a table showing the results of measuring the internal resistance at room temperature of 25° C. and current densities of 80 mA / g and 500 mA / g for an electricity storage device according to Comparative Example 4 (in which untreated activated carbon was used as an electrode) and an electricity storage device according to Example 4 of the present invention (in which low-resistance activated carbon was used as an electrode). [Figure 20] 1 is a graph showing charge / discharge curves (charge / discharge curves at current densities of 80 mA / g and 500 mA / g at −40° C.) of an electricity storage device according to Comparative Example 4 (untreated activated carbon was used as an electrode). [Figure 21]1 is a graph showing charge / discharge curves (charge / discharge curves at current densities of 80 mA / g and 500 mA / g at −40° C.) of Example 4 of the electricity storage device of the present invention (in which low-resistance activated carbon is used as an electrode). [Figure 22] 1 is a table showing the results of measuring the capacity at current densities of 80 mA / g and 500 mA / g at -40°C for an electricity storage device according to Comparative Example 4 (in which untreated activated carbon was used as an electrode) and an electricity storage device according to Example 4 of the present invention (in which low-resistance activated carbon was used as an electrode). [Diagram 23] 1 is a table showing the results of measuring the internal resistance at current densities of 80 mA / g and 500 mA / g at -40°C for an electricity storage device according to Comparative Example 4 (in which untreated activated carbon was used as an electrode) and an electricity storage device according to Example 4 of the present invention (in which low-resistance activated carbon was used as an electrode). [Figure 24] 13 is a graph showing the results of measuring the impedance of an electricity storage device of Comparative Example 4 (in which untreated activated carbon was used as an electrode) at room temperature of 25° C. and at −40° C. [Diagram 25] 13 is a graph showing the results of measuring the impedance of an electricity storage device of Example 4 of the present invention (in which low-resistance activated carbon is used as an electrode) at room temperature of 25° C. and at −40° C. [Figure 26] 13 is a table showing the impedance of an electricity storage device of Comparative Example 4 (in which untreated activated carbon was used as an electrode) at room temperatures of 25° C. and −40° C. [Figure 27] 13 is a table showing impedances at room temperatures of 25° C. and −40° C. of Example 4 of the electricity storage device of the present invention (in which low-resistance activated carbon is used as an electrode). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In the present invention, a method for treating activated carbon is achieved in which activated carbon and a carbon source that generates gaseous carbon when heated are simultaneously heat-treated, and the pyrolyzed carbon is adsorbed and attached to the surface of the activated carbon, thereby suppressing the adsorption capacity of the activated carbon and reducing gas generation. Also, an electricity storage device is achieved in which activated carbon treated by approximately this method for treating activated carbon is used as an electrode. EXAMPLES

[0014] The activated carbon treatment method of the present invention will be described with reference to an embodiment shown in FIG. The method for treating activated carbon in this embodiment is characterized in that activated carbon 1 and a carbon source 2 that generates gaseous carbon when heated are simultaneously heat-treated, and the pyrolyzed carbon source 2 is adsorbed and attached to the surface of the activated carbon 1. The treatment method will be described in detail below.

[0015] In the method for treating activated carbon in this embodiment, as shown in FIG. 1, activated carbon 1 was placed below a carbon source 2 that generates gaseous carbon when heated in a vessel 3, and a lid 4 was placed thereon for heat treatment.

[0016] The ratio of activated carbon 1 to carbon source 2 was set to 1:10, but is not limited to this and can be changed as appropriate.

[0017] Raw coke was used as the carbon source 2 that generates gaseous carbon when heated. However, the carbon source 2 that generates gaseous carbon when heated in the present invention is not limited to raw coke, and broadly includes carbon sources that generate gaseous carbon when heated.

[0018] The heat treatment temperature is preferably 450 to 1200°C. If the temperature is less than 450°C, gaseous carbon to be adsorbed from the carbon source 2 is not generated, and if the temperature exceeds 1200°C, the activated carbon 1 is altered and the specific surface area is significantly reduced. The heat treatment temperature is more preferably 800°C to 1100°C. If the temperature is less than 800°C, the resistance of the film formed on the activated carbon surface is not reduced, and if the temperature exceeds 1100°C, the film formed diffuses into the activated carbon, causing the low resistance film on the surface to be lost.

[0019] Specifically, in the embodiment shown in Fig. 1, activated carbon powder with an average particle size of 35 μm (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used as activated carbon 1, and the heat treatment was performed under nitrogen atmosphere at 1000°C for 2 hours. The temperature rise rate was 100°C / hour, and after the heat treatment was completed, the activated carbon 1 and the carbon source 2 were sieved to obtain a coated low-resistance activated carbon (treated activated carbon).

[0020] (Evaluation Test 1) The low-resistivity activated carbon (treated activated carbon: Pyrocoat) was evaluated by measuring and comparing the BET specific surface area, true density, total amount of functional groups, and Raman spectroscopy R value of the comparative example (untreated) and the low-resistivity activated carbon (Pyrocoat).

[0021] The BET specific surface area was measured using a multi-sample high-performance specific surface area / pore distribution analyzer (3Flex: manufactured by Micrometrics), which measures the specific surface area from the amount of nitrogen adsorbed by activated carbon 1. The true density was measured using a true density meter (AccuPic II 1345: manufactured by Shimadzu Corporation) using the dry method. The total amount of surface functional groups was measured by the Boehm method, in which the material was reacted with 0.1 mol / l sodium hydroxide solution and then titrated with 0.1 mol / l HCl solution. The crystallinity was evaluated by Raman spectroscopy (inVia: manufactured by Renishaw).

[0022] The results of evaluation test 1 are shown in Figure 2. The R value of Raman spectroscopy was calculated using the following formula.

[0023]

number

[0024] (Consideration) The specific surface area of ​​low-resistivity activated carbon (treated activated carbon: Pyrocoat) was reduced to about two-thirds by pyrolytic coating treatment, but the true density increased by about 17 percent. The amount of surface functional groups per weight was reduced to about one-third, and the amount per specific surface area was reduced to about one-half, confirming that the adsorption ability of the activated carbon was suppressed. The R value of Raman spectroscopy increased, suggesting that amorphous matter had accumulated on the surface. From these findings, it is presumed that a coating layer produced by pyrolytic coating treatment is formed on the surface of the activated carbon particles.

[0025] In addition, as shown in Figure 3 and Figure 4, although the pore distribution amount determined by nitrogen adsorption decreased, the profile showed a similar shape, and it was confirmed that the original pore structure was maintained (the low-resistance activated carbon (treated activated carbon: Pyrocoat) has the same pore profile as the activated carbon before treatment (comparative example (untreated))). Note that Figure 3 shows the results of pore distribution analysis by the BJH method, and Figure 4 shows the results of micropore analysis by the HK method.

[0026] (Evaluation Test 2) The low-resistance activated carbon (treated activated carbon: Pyrocoat) was evaluated by measuring and comparing the powder resistance of a comparative example (untreated) and the low-resistance activated carbon (Pyrocoat) by a microcompression test.

[0027] In the microcompression test of this embodiment, a microcompression tester (MCT-510 manufactured by Shimadzu Corporation) as shown in Fig. 5 was used to measure the compression behavior and resistance value of one powder particle for each of the comparative example (untreated) and the low-resistance activated carbon (treated activated carbon: Pyrocoat). Specifically, the compression load was measured while compressing one powder particle, and the resistance between the metal indenters 6 and 7 was measured at the same time. The test conditions were as follows: for the comparative example (untreated), the test force range was 20 mN, and the load speed (compression speed) was 0.446 mN / sec, and for the low-resistance activated carbon (treated activated carbon: Pyrocoat), the test force range was 100 mN, and the load speed (compression speed) was 1.937 mN / sec.

[0028] (Evaluation test 2 and results) The results of evaluation test 2 are shown in Figure 6. Since this is close to the contact resistance, the test force and resistance value at the point where the particles are deformed by 1% are also shown in Figure 7 and a comparison graph of the test forces is shown in Figure 8. The test force is the compression load when the powder is compressed by 1%, and the resistance value is the resistance value at that time.

[0029] (Consideration) It was confirmed that the resistance value of the low-resistance activated carbon (treated activated carbon: Pyrocoat) was reduced to 0.00024 times (0.024%) that of the comparative example (untreated) activated carbon, and that the resistance was significantly reduced (by about three orders of magnitude). It is presumed that the significant reduction in resistance was due to the adhesion (pyrolysis coating) of a carbon source that generates gaseous carbon when heated to the surface of the low-resistance activated carbon (treated activated carbon: Pyrocoat).

[0030] Next, an embodiment of the electricity storage device of the present invention will be described with reference to FIG. The electricity storage device 10 of this embodiment is an electricity storage device using, as electrodes (positive electrode 11 and negative electrode 12), low-resistance activated carbon having a carbon source (carbon) attached to the surface of the activated carbon 1, which generates gaseous carbon when heated. Each component will be described in detail below.

[0031] The electricity storage device 10 in this embodiment is an electric double layer capacitor (EDLC), but the electricity storage device of the present invention is not limited to an electric double layer capacitor and broadly includes electricity storage devices that use activated carbon as an electrode, and may be, for example, a lithium ion capacitor (LIC) or an air battery, in which case low-resistance activated carbon is used for the positive electrode.

[0032] Further, the electricity storage device 10 in this embodiment is a coin-type electric double layer capacitor, but is not limited to this and may be, for example, a pouch type or a cylindrical type.

[0033] The low-resistivity activated carbon is treated by the activated carbon treatment method of the present invention described above, and is obtained by pyrolytically coating (covering) the surface of the activated carbon 1 with the carbon source 2. That is, the low-resistivity activated carbon is obtained by adsorbing and attaching the carbon source 2 to the surface of the activated carbon 1 by simultaneously heat-treating the carbon source 2 and the activated carbon 1, and raw coke is used as the carbon source 2.

[0034] Specifically, the electrodes (positive electrode 11 and negative electrode 12) of the electricity storage device 10 of this embodiment were prepared by mixing low-resistance activated carbon, a conductive additive, and a binder solution (a solution of PVDF in NMP) in various combinations, coating an Al foil current collector 14, and vacuum drying at 120°C for 12 hours.

[0035] The electrodes (positive electrode 11 and negative electrode 12) were arranged facing each other, cellulose was used as a separator, and a 1M PC solution of TEMA·BF4 (triethylmethylammonium·tetrafluoroborate) was used as the electrolyte 13. The coin cell was assembled in a glove box in an Ar atmosphere to produce a coin-shaped electricity storage device (electric double layer capacitor) 10.

[0036] (Evaluation test 3 and results) The electricity storage device (electric double layer capacitor) 10 was evaluated using a charge / discharge evaluation device (HJ1001SD8: manufactured by Hokuto Denko Corporation) at room temperature of 25° C. The charge / discharge test was first performed by 50 cycles of charge / discharge at a current density of 80 mA / g, and then 5 cycles of charge / discharge at current densities of 12.5 mA / g to 1000 mA / g to evaluate the charge / discharge characteristics.

[0037] The ratio of activated carbon to binder was 9:1 by weight, and charge / discharge curves at a current density of 25 mA / g when no conductive additive was used are shown in Figures 10 and 11. Figure 10 shows untreated activated carbon (Comparative Example 1), and Figure 11 shows pyrocoated low-resistance activated carbon (Example 1).

[0038] In the case of untreated activated carbon, if no conductive additive was used, the voltage drop was large when switching from charging to discharging, the waveform became dull, and sufficient charge / discharge characteristics could not be obtained, as shown in Figure 10. On the other hand, in the case of using low-resistance activated carbon that had been subjected to pyrocoat treatment (Example 1), a charge / discharge curve similar to that of the normal battery was obtained, as shown in Figure 11.

[0039] (Evaluation test 4 and results) Next, the results of the capacity per weight at each current density when a conductive additive was added are shown in Figure 12. The ratio of activated carbon, conductive additive, and binder was 80:5:15.

[0040] When the activated carbon was untreated (Comparative Example 2), overshoot occurred, and charge / discharge curves could only be obtained up to a current density of 100 mA / g. However, when low-resistance activated carbon that had been pyrocoated (Example 2) was used, charge / discharge curves could be obtained up to a current density of 1000 mA / g.

[0041] (Evaluation test 5 and results) Furthermore, the ratio of the conductive additive in the coating-treated low-resistance activated carbon was changed to 89:1:10 (Example 3). The charge-discharge curves at a current density of 25 mA / g and 1000 mA / g for Example 3 are shown in Fig. 13 and Fig. 14, respectively. As shown in Fig. 13 and Fig. 14, good charge-discharge curves were shown at both a current density of 25 mA / g and a current density of 1000 mA / g, and it was confirmed that the capacity was maintained at 90% or more.

[0042] (Evaluation test 6 and results) The capacity retention rate is shown in Fig. 15, with the value at a current density of 12.5 mA / g taken as 100. Four types of samples are shown here: untreated activated carbon, and low-resistance activated carbon that has been pyrocoated, with a blend ratio (ratio of activated carbon:conductive additive:binder) of 80:5:15 (Comparative Example 2, Example 2), and 89:1:10 (Comparative Example 3, Example 3). It was confirmed that the capacity and performance were maintained in all of the samples that used low-resistance activated carbon that had been pyrocoated (Example 2, Example 3), even when the current density increased.

[0043] (Evaluation test 7 and results) Using untreated activated carbon and low-resistance activated carbon treated with pyrocoat, the electrodes were mixed (ratio of activated carbon:conductive additive:binder) at 80:10:10 (4 CMC, 6 SBR) in Comparative Example 4 and Example 4, which were fabricated by vacuum drying at 120°C for 12 hours using Al foil as a current collector. The above electrodes were placed opposite each other, cellulose was used as a separator, and a PC solution of 1M TEMA·BF4 (triethylmethylammonium·tetrafluoroborate) was used as the electrolyte to fabricate coin cells of Comparative Example 4 and Example 4. The coin cells were assembled in a glove box with an Ar atmosphere. The coin cells of Comparative Example 4 and Example 4 were evaluated using a charge / discharge evaluation device (HZ-Pro, manufactured by Meiden Hokuto Co., Ltd.) at room temperature of 25° C. In this charge / discharge test, 50 cycles of charge / discharge were performed at a current density of 80 mA / g, and then 5 cycles of charge / discharge were performed at current densities of 80 mA / g and 500 mA / g to evaluate the charge / discharge characteristics, and the result of the 5th cycle was used. As a result, for Comparative Example 4, the charge / discharge curve shown in Fig. 16 was obtained, and for Example 4, the charge / discharge curve shown in Fig. 17 was obtained, and the values ​​for both capacities were obtained as shown in Fig. 18. The internal resistance was calculated from the voltage drop when changing from charging to discharging, and the values ​​shown in Fig. 19 were obtained.

[0044] Next, the evaluation of Comparative Example 4 and Example 4 was carried out at a low temperature of −40° C. using a charge / discharge evaluation device (HZ-Pro: manufactured by Meiden Hokuto Co., Ltd.). The charge / discharge characteristics were evaluated by charging and discharging five cycles at current densities of 80 mA / g and 500 mA / g. As a result, for Comparative Example 4, the charge / discharge curve shown in Fig. 20 was obtained, and for Example 4, the charge / discharge curve shown in Fig. 21 was obtained, and the values ​​for both capacities were obtained as shown in Fig. 22. The internal resistance was calculated from the voltage drop when changing from charging to discharging, and the values ​​shown in Fig. 23 were obtained.

[0045] (Consideration) As shown in FIG. 18, the capacity of Comparative Example 4 at 25° C. was 26.68 F / g at a current density of 80 mA / g and 25.36 F / g at a current density of 500 mA / g, with a change of −4.95%, whereas the capacity of Example 4 at 25° C. was 23.89 F / g at a current density of 80 mA / g and 23.66 F / g at a current density of 500 mA / g, with a change of −0.97%, confirming that the capacity change with respect to current density was smaller in Example 4.

[0046] On the other hand, as shown in FIG. 22, the capacity of Comparative Example 4 at −40° C. was 25.68 F / g at a current density of 80 mA / g and 23.62 F / g at a current density of 500 mA / g, with a change of −8.05%, whereas the capacity of Example 4 at −40° C. was 21.45 F / g at a current density of 80 mA / g and 20.29 F / g at a current density of 500 mA / g, with a change of −5.41%, confirming that the change in capacity value relative to the current density of Example 4 was 2.64% lower.

[0047] As shown in FIG. 19, the internal resistance at 25° C. of Comparative Example 4 was 359.7 Ω at a current density of 80 mA / g and 54.0 Ω at a current density of 500 mA / g, whereas the internal resistance at 25° C. of Example 4 was 73.9 Ω at a current density of 80 mA / g and 21.7 Ω at a current density of 500 mA / g, confirming that Example 4 had a lower internal resistance.

[0048] On the other hand, as shown in FIG. 23, the internal resistance at −40° C. of Comparative Example 4 was 229.2 Ω at a current density of 80 mA / g and 119.7 Ω at a current density of 500 mA / g, whereas the internal resistance at −40° C. of Example 4 was 118.6 Ω at a current density of 80 mA / g and 75.0 Ω at a current density of 500 mA / g, confirming that Example 4 had a lower internal resistance.

[0049] (Evaluation test 8 and results) For evaluation of Comparative Example 4 and Example 4, the impedance was measured at room temperature of 25° C. and at a low temperature of −40° C. The impedance was measured using a measuring device (HZ-Pro: manufactured by Meiden Hokuto Co., Ltd.) at an applied voltage of 10 mV and a frequency of 100 kHz to 10 mHz, and the measurement results were analyzed by fitting using the following equivalent circuit (Table 1) with pyZwx (electrochemical impedance (Z) analysis software).

[0050] [Table 1]

[0051] For Comparative Example 4, the results shown in Figs. 24 and 26 were obtained, and for Example 4, the results shown in Figs. 25 and 27 were obtained.

[0052] (Consideration) As shown in Fig. 26, the impedance at 25°C in Comparative Example 4 was Rs 5.14Ω, R1 3.64Ω, and Rs+R1 8.78Ω, whereas as shown in Fig. 27, the impedance at 25°C in Example 4 was Rs 10.37Ω, R1 3.31Ω, and Rs+R1 13.68Ω, confirming that Example 4 had a higher impedance. However, it was confirmed that Example 4 had a lower R1, which indicates the contact resistance of activated carbon.

[0053] On the other hand, the impedance at -40°C in Comparative Example 4 was, as shown in Figure 26, Rs 30.48Ω, R1 10.19Ω, and Rs+R1 40.67Ω, whereas the impedance at -40°C in Example 4 was, as shown in Figure 27, Rs 10.62Ω, R1 9.03Ω, and Rs+R1 19.65Ω, confirming that Example 4 had a lower impedance.

[0054] From the above evaluation tests and results, it was confirmed that an electricity storage device using coated low-resistance activated carbon for electrodes has a small IR drop on both the charging and discharging sides, shows a good charge / discharge curve, and maintains capacity even when the current density increases and even without the use of a conductive additive. In addition, it was confirmed that an electric double layer capacitor using coated activated carbon for electrodes has a lower internal resistance even at low temperatures and a smaller change in capacitance value relative to current density compared to an electric double layer capacitor using untreated activated carbon for electrodes, and is therefore beneficial for use in automobiles in cold regions, for example. [Explanation of symbols]

[0055] 1 activated carbon 2. Carbon Source 3 Carbon Container 4 Lid 5. Micro-compression testing machine 6,7 Indenter 10. Energy storage devices 11 Positive electrode 12 Negative electrode 13 Electrolyte 14 Current collector

Claims

1. A method for treating activated carbon, comprising simultaneously heat-treating activated carbon and a carbon source which generates gaseous carbon when heated, and adsorbing and attaching the pyrolyzed carbon source to the surface of the activated carbon.

2. The method for treating activated carbon according to claim 1 , wherein the activated carbon obtained by the method for treating activated carbon has the same pore profile as the activated carbon before the treatment.

3. 3. The method for treating activated carbon according to claim 1, wherein the carbon source is pyrolyzed and adheres to a surface of the activated carbon, thereby lowering the resistance of the activated carbon.

4. 2. The method of claim 1, wherein the carbon source is raw coke.

5. 2. The method for treating activated carbon according to claim 1, wherein the temperature of the heat treatment is 450 to 1200°C.

6. 2. The method for treating activated carbon according to claim 1, wherein the temperature of the heat treatment is 800 to 1100°C.

7. 1. An electricity storage device, comprising: an activated carbon having a carbon source attached to its surface that generates gaseous carbon when heated; and said activated carbon being used as an electrode.

8. The electricity storage device according to claim 7 , wherein the carbon source is raw coke.

9. 9. The electricity storage device according to claim 7 or 8, wherein the activated carbon is heat-treated simultaneously with the carbon source, so that the pyrolyzed carbon source is adsorbed and attached to a surface of the activated carbon, and the activated carbon has the same pore profile as the activated carbon before the treatment and has a low resistance.

10. The electricity storage device according to claim 7 , wherein the electricity storage device is an electric double layer capacitor, a lithium ion capacitor, or an air battery.

11. 8. The electricity storage device according to claim 7, wherein the electricity storage device is an electric double layer capacitor, and the electric double layer capacitor uses, as an electrode, the activated carbon to which the carbon source that generates gaseous carbon when heated is attached to a surface of the activated carbon, and has a lower internal resistance even at low temperatures and a smaller change in capacitance value with respect to current density, compared to an electric double layer capacitor using the activated carbon before the treatment as an electrode.

Citation Information

Patent Citations

  • Secondary power source

    JP2003031220A

  • Method of manufacturing carbon material for electric double layer capacitor electrode

    JP2007115749A

  • Electric double layer capacitor

    JP2009272454A

  • Negative electrode material for nonaqueous lithium type energy storage element, and nonaqueous lithium type energy storage element using the same

    JP2011204901A

  • Manufacturing method of carbon coating electrode material for secondary battery, and carbon coating electrode material

    JP2011210649A